UJI AKTIVITAS PENANGKAPAN RADIKAL DPPH EKSTRAK PRODUK TEH HITAM (Camellia sinensis (L.) O.K.) DAN GAMBIR (Uncaria gambir (Hunter) Roxb) SERTA PROFIL KLT-DENSITOMETERNYA - I. G. N. I. P, Jaya,; N. P. E, Leliqia; Widjaja, I.N.K. (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012)
The purpose of this research was to compare the DPPH scavenging activity of black tea (Camellia sinensis (L.) OK) and gambier (Uncaria gambir (Hunter) Roxb) product extract and to determine their TLC-densitometer profile. This research was conducted in two stages, first stage was to examine the DPPH scavenging activity of black tea and gambier product extract. This assay used some concentrations of black tea product extract, gambier product extract, and standard vitamin C (10, 20, 40, 80, 160, 200, and 320 µg/mL). The second stage was to determine the extracts profile by TLC-densitometer. The result of this research showed that the DPPH scavenging activity of gambier product extract was greater (IC 50 = 88,57±0,64 µg/mL) than black tea product extract (IC 50 = 311,54±2,79 µg/mL). The result of profile determination of black tea product extract at a mobile phase of MeOH:toluene (50:50) showed that no spot was supposed a volatile oil group; at mobile phase of ethyl acetate:formic acid:acetic acid:H 2 O (100:11:11:26) showed two spots that was supposed a flavonoid group, spot with Rf 0,41 (? max 365 nm) and spot with Rf 0,97 (? max 280 nm); at mobile phase of CHCl 3 :MeOH (90:10) showed that spot with Rf 0,87 (? max 275 nm) was supposed an alkaloid group; at mobile phase of acetic acid:diethyl ether:n-hexane:ethyl acetate (20:20:20:40) showed that spot with Rf 0,62 (? max 290 nm) was supposed a tannin group. While the result of profile determination of gambier product extract at mobile phase of ethyl acetate:formic acid:acetic acid:H 2 O (100:11:11:26) showed two spots that was supposed a flavonoid group, spot with Rf 0,81 (? max 280 nm) and spot with Rf 0,92 (? max 280 nm); at mobile phase of acetic acid:diethyl ether:n-hexane:ethyl acetate (20:20:20:40) showed that spot with Rf 0,42 (? max 285 nm) was supposed a tannin group.
Keywords: Antioxidant, DPPH, black tea product, gambier product, TLC-densitometer profile